2016
DOI: 10.1590/0102-311x00166414
|View full text |Cite
|
Sign up to set email alerts
|

Walking, body mass index, and self-rated health in a representative sample of Spanish adults

Abstract: Obesity and physical inactivity (PI) are risk factors for chronic diseases and are associated with lifestyle and environmental factors. The study tested the association between PI, body mass index (BMI), and self-rated health in a representative sample of the Spanish adult population (N = 21,486). The sample included 41.5% men, with mean age 52.3 years (± 18.03), and age range 20-82 years. Prevalence of overweight/obesity was 34.2%/12.7% in women and 52.1%/12.7% in men (p < 0.001 for obesity in both sexes).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…Despite the well-established links between multiple health problems such as BMI, SRH, physical activity, and depressive symptoms (Okosun et al, 2001; Stunkard et al, 2003; Jokela et al, 2016; Romo-Perez et al, 2016), little is known about race by gender differences in the links between sustained health problems over time. The current study aimed to test if sustained high depressive symptoms and poor SRH similarly reflect sustained high BMI and physical inactivity in Black men and women and White men and women, using a nationally representative cohort of U.S. adults over age of 50.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the well-established links between multiple health problems such as BMI, SRH, physical activity, and depressive symptoms (Okosun et al, 2001; Stunkard et al, 2003; Jokela et al, 2016; Romo-Perez et al, 2016), little is known about race by gender differences in the links between sustained health problems over time. The current study aimed to test if sustained high depressive symptoms and poor SRH similarly reflect sustained high BMI and physical inactivity in Black men and women and White men and women, using a nationally representative cohort of U.S. adults over age of 50.…”
Section: Introductionmentioning
confidence: 99%
“… 15 By analyzing data obtained from the National Health and Nutrition Examination Survey 2005–2006, Lee et al 16 found that accelerometer-based active/high active groups (7,500 steps per day) had a significantly lower risk of depressive symptoms compared to sedentary groups (5,000 steps per day). In a representative sample of Spanish adults, Romo-Perez et al 17 showed that individuals who met the World Health Organization (WHO) guidelines for regular walking (≥150 minutes/week) had positive self-rated health and better body mass index (BMI) profile than those who did not meet the guidelines. In a 3-year prospective cohort study, Yoshida et al 18 assessed the association between habitual PA and depressive symptoms in Japanese older adults, and they found that sustained PA was an independent predictor for the incidence of depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…A associação entre atividade física e obesidade também foi verificada em um estudo conduzido na Espanha 56 . Mulheres que praticavam ≥ 150 minutos/semana de atividade física (fisicamente ativas) tiveram redução de 28% nas chances de obesidade em comparação às fisicamente inativas.…”
Section: ▄ Discussãounclassified